Effect of Apatyakara Ghrita Followed by Koshtha Shuddhi with Haritakyadi Churna in the Management of Ksheena Shukra w.s.r. to Oligozoospermia: A Case Study (AYUSHDHARA, 2021)
Oligozoospermia is a condition where sperm count is below 15 million/ml and a common finding which is related to male infertility. Some of the known responsible factors for male infertility are poor semen quality, genetic factors, testicular dysfunction and endocrine inter relationship etc. According to Ayurvedic classics, Oligozoospermia can be correlated with Ksheena Shukra which is due to increased Vata and Pitta Dosha being more prevalent in Madhyama Vayas. According to WHO, in India, the overall prevalence of primary infertility ranges between 3.9% and 16.8%.  Methods: In this study, a male patient aged 40 years was presented with a desire to get a child and other associated symptoms were Daurbalya (weakness), Mukha Shosha (dryness of the mouth), Sadana (loss of rigidity), Shrama (post act exhaustion), Alpachestata (early ejaculation), Maithune Ashakti (problematic or not satisfactory coitus), Rati Anabhimukhata (loss of sexual desire) etc. The patient was managed with Apatyakara Ghrita followed by Koshtha Shuddhi with Haritakyadi Churna. For the assessment of the effect of therapies on sexual parameters, the scoring pattern prepared by Mehra & Singh, 1995 and Seminal Parameters has been adopted. Results and Conclusion: Apatyakara Ghrita is found effective to increase sperm count from 12 million/ ml to 45 million/ml and motility from 20% to 75% and no adverse effect of the adopted management was seen during treatment and even after the 2 months of follow-up.